AKT Hyperphosphorylation and T Cell Exhaustion in Down Syndrome - Peeters, Daphne; Pico-Knijnenburg, Ingrid; Wieringa, Douwe; Rad, Mandana; Cuperus, Roos; Ruige, Madelon; Froeling, Frank; Zijp, Gerda W.; van der Burg, Mirjam; Driessen, Gertjan J. A. (Frontiers in Immunology, 2022)
Down syndrome (DS) is associated with increased susceptibility to infections, auto-immunity, immunodeficiency and haematological malignancies. The exact underlying immunological pathophysiology is still unclear. The immunophenotype and clinical characteristics of DS resemble those of Activated PI3K Delta Syndrome (APDS), in which the PI3K/AKT/mTOR pathway is overactivated. We hypothesized that T cell exhaustion and the hyperactivation of the AKT signalling pathway is also present in immune cells of children with DS. In this observational non-interventional cohort study we collected blood samples of children with DS (n=22) and healthy age-matched controls (n=21) for flowcytometric immunophenotyping, phospho-flow AKT analysis and exhaustion analysis of T cells. The median age was 5 years (range 1-12y). Total T and NK cells were similar for both groups, but absolute values and transitional B cells, naive memory B cells and naive CD4+ and CD8+ T cells were lower in DS. pAKT and AKT were increased for CD3+ and CD4+ T cells and CD20+ B cells in children with DS. Total AKT was also increased in CD8+ T cells. Children with DS showed increased expression of inhibitory markers Programmed cell dealth-1 (PD-1), CD244 and CD160 on CD8+ T cells and increased PD-1 and CD244+ expression on CD4+ T cells, suggesting T cell exhaustion. Children with DS show increased pAKT and AKT and increased T cell exhaustion, which might contribute to their increased susceptibility to infections, auto immunity and haematological malignancies.